2009
DOI: 10.1093/ejo/cjp068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bisphosphonates on orthodontic tooth movement in mice

Abstract: Mechanical stress such as orthodontic tooth movement induces osteoclastogenesis. Sometimes, excessive mechanical stress results in root resorption during orthodontic tooth movement. It has been reported that bisphosphonate inhibits osteoclastogenesis. Recently, there have been concerns for orthodontic patients receiving bisphosphonates. Thus, the aim of this study was to investigate the effect of bisphosphonates on orthodontic tooth movement and root resorption in mice. A nickel-titanium (Ni-Ti) closed coil sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
57
0
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 33 publications
2
57
0
6
Order By: Relevance
“…A recent study by Fujimura et al 22 has been reported that the local administration of alendronate sodium hydrate has inhibited orthodontic tooth movement and root resorption in male mice. Classically, ovariectomized rats have been advocated as a good osteoporotic animal model 23 and often have been used to study efficacy of drugs aimed to prevent bone loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Fujimura et al 22 has been reported that the local administration of alendronate sodium hydrate has inhibited orthodontic tooth movement and root resorption in male mice. Classically, ovariectomized rats have been advocated as a good osteoporotic animal model 23 and often have been used to study efficacy of drugs aimed to prevent bone loss.…”
Section: Introductionmentioning
confidence: 99%
“…30 Therefore, the medications and other substances have been used to inhibit the bone resorption such as bisphosphonates might show an effect on the prevention of root resorption during orthodontic treatment. 22 In the last 20 years, the number of adult orthodontic patients has dramatically increased. 31 However, the studies about pharmaceuticsorthodontics in adult orthodontic patients, especially in postmenopausal patients, have never been completely elucidated due to the continually developing drugs and drug regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Borah et al 5 evaluated changes in bone mineralization and architecture in postmenopausal women with osteoporosis after long-term treatment with risedronate, elucidating normalization of mineral levels. The effect of bisphosphonates on orthodontic tooth movement (OTM) has also been investigated in some reports, [6][7][8][9][10] in which administration of bisphosphonates decreased OTM.…”
mentioning
confidence: 99%
“…Hasil ini menunjukkan bahwa BP mungkin berguna untuk mengontrol pergerakan gigi ortodontik dan sebagai kandidat penghambat resorpsi akar selama pergerakan gigi ortodontik. 21 Namun, efek lain dari penggunaan BP adalah adanya kemungkinan hambatan pergerakan gigi yang dirawat ortodontik (Gambar 2). 21 Selanjutnya, data menunjukkan bahwa konsumsi BP meningkatkan waktu yang dibutuhkan untuk perawatan ortodontik dan mempengaruhi keberhasilan perawatan ortodontik dalam hal penutupan ruangan dan paralelitas akar.…”
unclassified
“…21 Namun, efek lain dari penggunaan BP adalah adanya kemungkinan hambatan pergerakan gigi yang dirawat ortodontik (Gambar 2). 21 Selanjutnya, data menunjukkan bahwa konsumsi BP meningkatkan waktu yang dibutuhkan untuk perawatan ortodontik dan mempengaruhi keberhasilan perawatan ortodontik dalam hal penutupan ruangan dan paralelitas akar. 22 Penelitian yang mengevaluasi efek pemberian topikal chlodronat pada tulang alveolar hewan coba yang mengalami periodontitis, menunjukkan bahwa obat ini mencegah kehilangan tulang dan menurunkan jumlah osteoklas.…”
unclassified